Ribavirin-induced mutagenesis across the complete open reading frame of hepatitis C virus genotypes 1a and 3a - Mejer, Niels; Fahnøe, Ulrik; Galli, Andrea; Ramirez, Santseharay; Benfield, Thomas; Bukh, Jens (Journal of general virology, 2018)
Ribavirin (RBV) has been used for the last 20 years to treat patients with chronic hepatitis C virus (HCV) infection. This pluripotent drug is believed to induce mutagenesis in HCV RNA. However, for cell-cultured HCV (HCVcc) this phenomenon has only been investigated in genotype 2a recombinants. Here we studied the mutations that developed in HCVcc of genotypes 1a and 3a treated with RBV or ribavirin triphosphate (RBV-TP) compared to non-treated controls. Analysis was performed on the amplified full-length open reading frame (ORF) of recovered viruses following next-generation sequencing and clonal analyses. Compared to non-treated controls, the spread of TNcc(1a) and DBN3acc(3a) HCVcc was delayed by RBV and RBV-TP at concentrations of 40 µM or higher. The delay in HCVcc spread was associated with increased new single-nucleotide polymorphisms (SNP). Significantly higher numbers of new SNP were observed in TNcc(1a) viruses treated with RBV or RBV-TP compared to matched non-treated controls. RBV or RBV-TP treatment led to significantly increased proportions of new G-to-A and C-to-U SNP compared to non-treated TNcc(1a). Clonal analyses confirmed a significantly increased mutation rate in RBV-treated TNcc(1a). Synonymous pairwise distances increased in both viruses across the complete ORF under RBV and RBV-TP treatment compared to controls. Consensus-shifts in single samples of RBV- or RBV-TP-treated TNcc(1a) viruses occurred in proteins E1, p7, NS3 and NS4B. No non-synonymous consensus changes were observed in DBN3acc(3a). This study supports a biased G-to-A and C-to-U mutagenic effect of RBV and RBV-TP throughout the entire ORF of HCV genotypes 1a and 3a.